Analisa dan Implementasi Sistem Informasi Pengeluaran Kas Kecil Pada PT. Bank Bukopin Berbasis Web - Yuni Eka Achyani; Anggi Velayati (Paradigma, 2020)
The application of a petty cash disbursement information system in a company is very important because by applying the petty cash disbursement information system, the company can supervise and control the course of the company's operational activities so that it can run as it should. This study aims to find out how the petty cash fund accounting system applied at PT. Bank Bukopin West Bekasi, is it in accordance with SOP (operational standards) in the company, and to find out the weaknesses of the system that is already running. From the results of this study obtained a discussion that in the petty cash expenditure PT. Bank Bukopin West Bekasi is still done manually starting from recording data to storing other data relating to the petty cash disbursement process to reporting. The research method used by the author is to use field research, interview methods and library methods while the software development method used by the writer is the waterfall method with the SDLC model. So according to the research of PT. Bank Bukopin West Bekasi requires a system that is expected to produce better reports in support of petty cash activities. The programming language used in development is to use a MySQL database and an editor using Notepad ++. This research will discuss about a web-based petty cash expenditure information system that is how the submission process, reimbursement, capital and reports. The author's purpose of this research is a small cash expenditure information system with the hope that it can overcome the obstacles that have occurred in the small cash expenditure system manually, and can assist in the process of making reports.